2004
DOI: 10.1002/prot.20179
|View full text |Cite
|
Sign up to set email alerts
|

Modeling correlated main‐chain motions in proteins for flexible molecular recognition

Abstract: We describe a new method for modeling protein and ligand main-chain flexibility, and show its ability to model flexible molecular recognition. The goal is to sample the full conformational space, including large-scale motions that typically cannot be reached in molecular dynamics simulations due to the computational intensity, as well as conformations that have not been observed yet by crystallography or NMR. A secondary goal is to assess the degree of flexibility consistent with protein-ligand recognition. Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 73 publications
1
75
0
Order By: Relevance
“…We also compared the rigid clusters formed by FIRST for barnase from previous work [28,27,36] and found that the largest rigid cluster identified by FIRST consisting of α1 helix and β1-β5 indeed exhibited overall smaller distance fluctuations in DTA. We also note that comparing our results with that of FIRST for cyclophilin A [47], we found good agreement in terms of the location of flexible versus constrained regions in the enzyme.…”
Section: Comparing With Experimental/ Theoretical Worksupporting
confidence: 65%
“…We also compared the rigid clusters formed by FIRST for barnase from previous work [28,27,36] and found that the largest rigid cluster identified by FIRST consisting of α1 helix and β1-β5 indeed exhibited overall smaller distance fluctuations in DTA. We also note that comparing our results with that of FIRST for cyclophilin A [47], we found good agreement in terms of the location of flexible versus constrained regions in the enzyme.…”
Section: Comparing With Experimental/ Theoretical Worksupporting
confidence: 65%
“…This was the problem encountered in neutral endopeptidase; as alluded to, the problem can be partly addressed by generating multiple ensembles based on multiple different rigid fragments, [34] or by altering the location of the docking spheres and possibly performing multiple docking calculations. Finally, this method had not been investigated heavily in the context of allowing for receptor flexibility, as other methods have done [11,13,[36][37][38][39][40] (though see ref. [41]).…”
Section: Methodological Caveatsmentioning
confidence: 99%
“…Ligands can then be independently docked into each protein conformation using SLIDE, 43 as was demonstrated for fully flexible docking of the cyclic peptide cyclosporin with its receptor, cyclophilin A. 44 StoneHingeP already provides the input files needed by ROCK, making the process easy to automate.…”
Section: Using Stonehinge To Guide Flexible Dockingmentioning
confidence: 99%